Pengaruh Perilaku Extrarole (Organization Citizenship Behavior/OCB) Dan Motivasi Kerja Terhadap Kinerja Pegawai Dengan Mediasi Kepuasan Kerja (Kasus Pada Terminal Peti Kemas Semarang) (Jurnal Mahasiswa Pasca Sarjana, 2014)
Container Terminal in Semarang is a state-owned enterprise ( SOE ) which specifically serves the container handling activities where one activity is the loading and unloading of containers from ship to dock and vice versa from the dock to the ship . Currently the company is faced with the problems that led to a decrease in employee performance overall company performance is also affected . The decline in the company 's performance is shown by the amount of work that is not timely , so the company's operational performance is also declining . The purpose of this study is to examine and analyze the effect of organization citizenship behavior and motivation on employee performance with the mediation of job satisfaction on employee Container Terminal in Semarang . This study focused on employee Container Terminal in Semarang , the questionnaire method of data collection , sample by purposibe sampling , the statistical method of path analysis. The results showed that ( 1 ) OCB ( Organization Citizenship Behavior ) had no significant effect on job satisfaction .. ( 2 ) Work Motivation significant positive effect on job satisfaction The better job motivation factors will affect the employee job satisfaction in completing the work. ( 3 ) OCB ( Organization Citizenship Behavior ) significantly affects employee performance, the better the factors of OCB ( Organization Citizenship Behavior ) will affect on improving employee performance. ( 4 ) Work Motivation significant effect on the performance of employees ( 5 ) Job Satisfaction significant effect on performance employee, the better the job satisfaction factors will affect the improvement of employee performance . Keywords : Behavior Extrarole ( Organization Citizenship Behavior / OCB ) Work Motivation,    Employee Performance, Job Satisfaction ( Case In Container Terminal Semarang )